Comparison of the efficacy of ethylenediaminetetraacetic acid and tetracycline hydrochloride as root conditioning agents: An in vitro study - Tarun Nanda; Sanjeev Jain; Daljit Kapoor; Harjit Kaur; Sonia Nanda (Wolters Kluwer Medknow Publications, 2012)
Objective: Root surfaces of periodontitis-affected teeth are hypermineralized and contaminated with cytotoxic and other biologically active substances. Various root conditioning agents have been recommended as an adjunct to mechanical root surface debridement to expose dentin collagen and cementum bound proteins. The aim of the present in vitro study was to compare the efficacy of ethylenediaminetetraacetic acid (EDTA) and tetracycline hydrochloride (HCl) as root conditioning agents on planed root surfaces. Materials and Methods: A total of 20 human maxillary anterior teeth indicated for extraction due to chronic periodontitis were collected and root planed. The teeth were sectioned and specimens were divided into two groups - Group I and II. Group I dentin specimens were treated with EDTA and Group II specimens were treated with tetracycline HCl solution at a concentration of 10% by active burnishing technique for 3 min. The root surface samples were then examined by scanning electron microscope. Results: The results of this study showed that EDTA and tetracycline HCl were equally effective in removing the smear layer. It was observed that the total and patent dentinal tubules were more in number in teeth treated with tetracycline when compared to EDTA group. However, EDTA was found to be much more effective as root conditioning agent because it enlarged the diameter of dentinal tubules more than that of tetracycline HCl. Conclusion: The results of in vitro study showed that both the agents are good root conditioning agents if applied in addition to periodontal therapy. However, further studies are required to establish the in vivo importance of EDTA and tetracycline HCL as root conditioners.